2010
DOI: 10.1111/j.1365-2567.2009.03225.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in neurodegenerative diseases

Abstract: Summary Neurodegeneration, the slow and progressive dysfunction and loss of neurons and axons in the central nervous system, is the primary pathological feature of acute and chronic neurodegenerative conditions such as Alzheimer’s disease and Parkinson’s disease, neurotropic viral infections, stroke, paraneoplastic disorders, traumatic brain injury and multiple sclerosis. Despite different triggering events, a common feature is chronic immune activation, in particular of microglia, the resident macrophages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
858
0
24

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,174 publications
(886 citation statements)
references
References 115 publications
(200 reference statements)
4
858
0
24
Order By: Relevance
“…Pathways transduced by the activation of TNF receptor-1 are linked to the induced expression of COX-2 [23] . Furthermore, these cytokines may stimulate the expression of [24] . This process may lead to the production of toxic amounts of NO free radicals, which in turn could potentiate the expression and release of TNF-α by adjacent microglial cells and thereby further amplify the inflammatory reaction [15,25] .…”
Section: Discussionmentioning
confidence: 99%
“…Pathways transduced by the activation of TNF receptor-1 are linked to the induced expression of COX-2 [23] . Furthermore, these cytokines may stimulate the expression of [24] . This process may lead to the production of toxic amounts of NO free radicals, which in turn could potentiate the expression and release of TNF-α by adjacent microglial cells and thereby further amplify the inflammatory reaction [15,25] .…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, in an ante-mortem study, no change was observed in the NE levels in the frontal cortex, but significant decrease was observed in the temporal cortex [180]. Loss of norepinergic neurons of the LC and subsequent loss of norepinephrine have a pro-inflammatory effect in animal models [181]. Moreover, observation suggests, stimulation of the microglia with norepinephrine leads to enhanced phagocytosis of amyloid-β (Aβ) [181].…”
Section: Review Amarendranath Choudhurymentioning
confidence: 99%
“…Loss of norepinergic neurons of the LC and subsequent loss of norepinephrine have a pro-inflammatory effect in animal models [181]. Moreover, observation suggests, stimulation of the microglia with norepinephrine leads to enhanced phagocytosis of amyloid-β (Aβ) [181]. Therefore, alterations of the norepinergic system contribute partially to the neuroinflammation associated with AD and the subsequent consequences [181].…”
Section: Review Amarendranath Choudhurymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to other tissues, the blood-brain barrier (BBB) largely avoids the infiltration of T cells from capillaries. Moreover, astrocytes and neurons are able to suppress T cell activation and even induce apoptosis in T cells [43]. The reason for this Bimmune privilege^in the brain is attributed to its sensitivity and restricted regenerative capacity compared to other tissues.…”
Section: Introductionmentioning
confidence: 99%